2017
DOI: 10.1063/1.4997762
|View full text |Cite
|
Sign up to set email alerts
|

Ag fractal structures in electroless metal deposition systems with and without magnetic field

Abstract: Metal electrodeposition systems display tree-like structures with extensive ramification and a fractal character. Electrolysis is not a necessary route for the growth of such dendritic metal deposits. We can grow beautiful ramification patterns via a simple redox reaction. We present here a study of silver (Ag) deposits from the reduction of Ag in (AgNO) solution by metallic copper. The experiments are carried out in discotic geometry, in a Petri dish hosting a thin AgNO solution film. A variety of deposited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In the study of magnetic effects, the magnetic field intensity and direction dependencies of systems are generally interesting subjects. In fact, such dependencies were investigated for pattern formation in silver dendrite systems. , Unfortunately, because the painting-out effect observed here was basically minimal and considerably stochastic, it is difficult to accurately examine these dependencies using the present setup. Details of the dependencies need to be investigated further using a high-power, superconducting electromagnet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of magnetic effects, the magnetic field intensity and direction dependencies of systems are generally interesting subjects. In fact, such dependencies were investigated for pattern formation in silver dendrite systems. , Unfortunately, because the painting-out effect observed here was basically minimal and considerably stochastic, it is difficult to accurately examine these dependencies using the present setup. Details of the dependencies need to be investigated further using a high-power, superconducting electromagnet.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, Zhao et al 13 found that a static magnetic field (0.4 T) could change the geometric morphologies of the Liesegang bands of silver dendrite observed on the surface of a liquid. Very recently, Ibrahim et al 14 studied the magnetic-field-induced effect on the fractal structures of silver dendrite and discussed the differences between their results and those of Zhao et al 13 To the best of our knowledge, the effect of a magnetic field on the Liesegang bands that form in the gel media (i.e., the traditional Liesegang bands) has not been reported yet.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We observe random oscillations in the spacing sequence, and compute the entropy of this self-organizing system, which is shown to be consistent in all the considered sets. The present work is an extension of our previous work on electrolytic fractal growth in Zn [ 20 ], and two-metal [ 21 , 22 ] systems, and electroless growth of Ag by reduction of Ag + with Cu [ 23 ].…”
Section: Introductionmentioning
confidence: 93%
“…The random walker moves until it reaches a site adjacent to the seed and sticks there, consequently forming a cluster. The effect of external factors like pressure [11,12], temperature [13], electric field [14][15][16][17][18] and magnetic field [19][20][21] on the DLA patterns have been studied by several groups. Fractal patterns with copper and silver aggregates have been obtained by simple displacement reaction [22,23] and chemical dissolution methods [24] in the absence of any external stimuli.…”
Section: Introductionmentioning
confidence: 99%